Augmented Reality with Speech Recognition for Animal Recognition Applications - Aldia Deponsa Judistira; Agus Pratondo; Anang Sularsa (IJAIT (International Journal of Applied Information Technology), 2022)
The advance of educational technology is significantly changing and is very effective in supporting education nowadays. However, technology to support education in Indonesia is not maximal; one of the cases occurred in the PGRI Sumedang Kindergarten. Teachers at PGRI Sumedang Kindergarten have difficulties providing material that can build students’ interest, especially general knowledge about animals. This study aims to design Augmented Reality (AR) technology features with Speech Recognition for an Android-based interactive multimedia application of animal knowledge to assist learning activities in PGRI Sumedang Kindergarten. AR is a computer technology that combines virtual objects with the real world. This AR feature uses a card-shaped marker with an image and speech recognition as a medium for interaction with animals. Speech recognition is a computer technology to process human speech into digital letters or words. The resulting interaction is that if the user pronounces the animal’s name displayed in AR, the animal animation will move. This AR feature can help to learn activities at Kindergarten PGRI Sumedang.